LGBTQ College student health and wellbeing at the onset of the pandemic: additional evidence and lessons learned from COVID-19 - Gilbert Gonzales; Emilio Loret de Mola; Lee Robertson; Kyle A. Gavulic; Tara McKay (BMC, 2023)
Abstract Background The coronavirus (COVID-19) pandemic has killed more than six million people and disrupted health care systems globally. In the United States alone, more than one million people have died from COVID-19 infections. At the start of the pandemic, nearly all aspects of our lives paused to prevent the spread of the novel coronavirus. Many institutions of higher education transitioned to remote learning and enacted social distancing measures. This study examined the health needs and vulnerabilities of lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQ) college students at the start of the COVID-19 pandemic in the United States. Methods We fielded a rapid-response online survey between April and June of 2020. We recruited 578 LGBTQ-identifying college students aged 18 years and older by reaching out to LGBTQ-serving organizations on 254 college campuses and via targeted social media advertising. Results Approximately 40% of LGBTQ college students surveyed were dissatisfied with life at the start of the COVID-19 pandemic, and almost all (90%) were concerned that COVID-19 would threaten their mental health. Moreover, about 40% of LGBTQ college students reported unmet mental health needs, and 28% were worried about seeking care during the pandemic because of their LGBTQ identity. One out of four LGBTQ college students had to go back in the closet because of the pandemic, and approximately 40% were concerned about their finances or personal safety during the COVID-19 pandemic. Some of these adverse outcomes were prominent among younger students, Hispanic/Latinx students, and students with unsupportive families or colleges. Conclusions Our study adds novel findings to the large body of research demonstrating that LGBTQ college students experienced distress and elevated mental health needs early in the pandemic. Future research should examine the long-term consequences of the pandemic among LGBTQ and other minoritized college students. Public health policymakers, health care providers, and college and university officials should provide LGBTQ students affirming emotional supports and services to ensure their success as the COVID-19 pandemic transitions to endemic.